How does pasture management affect the metabolomic profile of bovine milk? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University, Palmerston North, New Zealand. EMBARGOED until 18th February 2027. - White, Bradley Jason (Massey University, 2025)
The dairy industry is essential to the economy of New Zealand and is embracing more advanced technologies to drive value in dairy exports. This includes the development of rapid metabolic profiling methods that can link on-farm conditions to nutritional outcomes of the milk and downstream processed dairy products. In this study, an untargeted milk metabolomics LC-MS/MS pipeline was optimised to increase the throughput of high accuracy metabolite identifications. Enhancements included automation of sample preparation, construction of a comprehensive in-house metabolite library and thorough profiling of every m/z signal generated from the analysis of raw milk. The methodology was tested on real raw milk samples from different NZ farms, and cross validated with a secondary technique (NMR spectroscopy). High throughput was achieved, with hands-on sample preparation time reduced by 75% (15 minutes per sample) and 60% of all m/z signals being automatically assigned (increased from 0%). The methodology was deployed to find biomarkers of cows grazing diverse (regenerative) pasture species, including unambiguous identification of nutritionally beneficial bioactive compounds not previously known in milk. The method successfully differentiated the milk from the two different feeding regimes based on the profile of small molecules (metabolites).
Embargoed until 18th February 2027 Figure 36 is reused with permission.
Keywords: 340106 Metabolomic chemistry; 340502 Natural products and bioactive compounds